Analisis Yuridis Tanggung Jawab Notaris Terhadap Tindak Pidana Pemalsuan Akta Otentik (Studi Penelitian di Kota Batam) - Erlys, Erlys; Fadlan, Fadlan; Nofrial, Ramon; Respationo, Soerya; Erniyanti, Erniyanti (UNES Law Review, 2023)
The implementation of the Notary's duties and position is based on the high level of integrity and honesty of the Notary, the results of the work in making deeds and maintaining protocols as authentic evidence regarding the interests of justice seekers, both personal interests and business interests, so that the implementation of the Notary's duties and positions must be supported by moral will. which can be accounted for. The problem of this research: what are the legal regulations regarding the procedures for making authentic deeds by Notaries as Public Officials, the legal relationship between Notaries and Facing Parties in making authentic deeds, as well as the Notary's legal responsibility for authentic deeds in connection with criminal acts of forgery? Notary is a Public Official, authorized to make authentic deeds regarding all acts, agreements and stipulations which are required by a general regulation to be stated in an authentic deed, guarantee certainty of date, keep the deed and provide grosses, copies and quotations throughout the making of such a deed by a general rule is also not assigned or excluded to officials or other people. The presenter comes to the Notary, so that the actions or deeds are formulated into an authentic deed according to the authority of the Notary, and then the Notary makes a deed at the request or desire of the Presenter, in this case providing a basis for the Notary and the Presenter that a legal relationship exists. The legal responsibility of a Notary as a Public Official regarding authentic deeds related to criminal acts of forgery is: A Notary can be said to be free from legal responsibility if the authentic deed he has made and/or executed in front of him has fulfilled the formal requirements. If the Notary is proven to have violated the provisions of the law, namely fulfilling the criminal elements contained in the Criminal Code, then the notary can be held criminally responsible. Notaries in carrying out their duties must be careful, act honestly, impartially, and safeguard the interests of related parties. In making a deed, introduce the person present, based on identity, ask, then listen and pay attention to the wishes of the parties, examine documentary evidence, provide suggestions and create a framework for the deed to fulfill the wishes or desires of the parties, fulfill all administrative techniques for making the deed such as reading, signing, provide copies and filings for minutes, and carry out other obligations related to the duties of the Notary position.